Knowledge, attitudes and practices associated with post-natal PMTCT in breastfeeding mothers living with HIV - Phumzile Dlamini; Theresa S. Mokoboto-Zwane (Elsevier, 2019)
Despite interventions tailored to prevention of mother-to-child of HIV and reported improvements on the outcomes, there is still vertical transmission of HIV through breastfeeding. The study sought to explore knowledge, attitudes, and practices of breastfeeding mothers living with HIV regarding post-natal PMTCT interventions and services. The study sample size was 90 and included conveniently selected breastfeeding mothers living with HIV who attended the King Sobhuza II public health unit for post-natal healthcare services in the Manzini region of Eswatini (formally known as Swaziland). Data were collected by administering a questionnaire to selected participants. The Statistical Package for the Social Science (SPSS version 20) was utilized for capturing raw data and then analyzed using tabulation and frequencies (descriptive statistics). The overall study results revealed that a majority of breastfeeding mothers living with HIV (77.8%) presented with high levels of knowledge on PMTCT, 90% demonstrated a positive attitude and 90% demonstrated a positive behaviour towards PMTCT. However, stigma and discrimination among family members, non-disclosure of HIV status to sexual partners; as well as poverty and fear of future drug-resistance were reported as risk factors of non-adherence to ARV prophylaxis. Furthermore, inconsistent condom use, mixed-feeding methods, and wet-nursing also emerged as other contributing factors to the increase of post-natal transmission of HIV among breastfeeding mothers living with HIV. Low knowledge of less than 50% regardless of educational background was noted on specific questions which will invariably influence the respondents' attitudes and practices, increasing their babies' risks of acquiring HIV during breastfeeding. Keywords: Breastfeeding, HIV/AIDS, PMTCT attitude, PMTCT knowledge, PMTCT practices